Eating the Gospel: Food for Thought in Romanos the Melodist - Arentzen, Thomas (Journal of the International Society for Orthodox Music, 2024)
A series of seven interconnected meditations reflects on what eating, drinking, and tasting could mean for Christian theologizing. What might be the ecological implications of a theology that takes eating and digestion more seriously? The reflections are carried out in company with Romanos the Melodist and the broader Romanos tradition.